2020
DOI: 10.1155/2020/2372746
|View full text |Cite
|
Sign up to set email alerts
|

Dose Correlation of Danggui and Chuanxiong Drug Pairs in the Chinese Medicine Prescription Based on the Copula Function

Abstract: Dosage is essential for studying the compatibility and effectiveness of traditional Chinese medicine. Danggui and Chuanxiong are widely used in traditional Chinese medicine for ailments and treatment of various disorders. 628 traditional Chinese medicine prescriptions containing Danggui and Chuanxiong were extracted from the self-built prescription database and screened for the three groups of prescriptions, i.e., irregular menstruation, sores, and stroke. We processed and tested the dosage of Danggui and Chua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The copula function model analysis results showed that, in the three groups of prescriptions for treating irregular menstruation, sores, and stroke, the doses of Chuanxiong and Danggui were all positively correlated. These results also indicate that the copula function model was suitable for analyzing the dose correlation in TCM [ 26 ].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The copula function model analysis results showed that, in the three groups of prescriptions for treating irregular menstruation, sores, and stroke, the doses of Chuanxiong and Danggui were all positively correlated. These results also indicate that the copula function model was suitable for analyzing the dose correlation in TCM [ 26 ].…”
Section: Discussionmentioning
confidence: 88%
“…Some prescriptions were also selected from 414 famous doctors in modern times, including some hospitals and pharmaceutical factories. Finally, 51083 prescriptions (the entire database) were included in our prescription database [ 26 ]. Figure 1 shows the study process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we can see in Figure 11A, their MSD curves are very similar. The results of 45 prescriptions containing Chuanxiong and Danggui analyzed by Gumbel copula function model showing that the Chuanxiong and Danggui have a strong nonlinear correlation in stroke, and the correlation is positive [18]. Studies have shown that their extracts exert neuronal protective effects by promoting endogenous proliferation of neuroblastoma cells and production of neural differentiation factors after ischemic injury from stroke in rats [19]- [20].…”
Section: Time Series Analysismentioning
confidence: 99%